2002
DOI: 10.1038/oby.2002.58
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Body Mass Index, Cardiorespiratory Fitness, and All‐Cause Mortality in Women

Abstract: The relation of body mass index, cardiorespiratory fitness, and all-cause mortality in women. Obes Res. 2002;10:417-423. Objective: To examine the relation of body mass index (BMI), cardiorespiratory fitness (CRF), and all-cause mortality in women. Research Methods and Procedures:A cohort of women (42.9 Ϯ 10.4 years) was assessed for CRF, height, and weight. Participants were divided into three BMI categories (normal, overweight, and obese) and three CRF categories (low, moderate, and high). After adjustment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(125 citation statements)
references
References 19 publications
5
117
2
1
Order By: Relevance
“…Results of other prospective studies in men and women further suggest that high levels of physical activity protect against the incidence of coronary artery disease, independent of BMI, as well as other factors such as age, smoking, diabetes and hypertension (62). Furthermore, prospective analyses from the Aerobics Center Longitudinal Study have consistently reported that CRF is a significant predictor of mortality from all causes (9,10,63,64), CVD (9,10) and type 2 diabetes (65) in men and women, independent of BMI or WC. These relationships have been confirmed in older adults (66) and Canadian women (67).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 89%
“…Results of other prospective studies in men and women further suggest that high levels of physical activity protect against the incidence of coronary artery disease, independent of BMI, as well as other factors such as age, smoking, diabetes and hypertension (62). Furthermore, prospective analyses from the Aerobics Center Longitudinal Study have consistently reported that CRF is a significant predictor of mortality from all causes (9,10,63,64), CVD (9,10) and type 2 diabetes (65) in men and women, independent of BMI or WC. These relationships have been confirmed in older adults (66) and Canadian women (67).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 89%
“…The second dependent variable combined BMI and physical activity to identify the highest risk (obese and inactive) and lowest risk (normal weight and active) subgroups. 24,26 Overweight was not included in the main analysis because, compared with obesity, the health effects are unclear 34 and there is a greater potential to misclassify lean, muscular persons (especially men) into this group. 35 For completeness, however, additional analyses were performed to examine overweight vs normal weight, and the findings are discussed in brief.…”
Section: Methodsmentioning
confidence: 99%
“…Second, recent research indicates that high levels of physical activity (or cardiorespiratory fitness) may attenuate the negative health burden of obesity. [23][24][25][26] As yet, environmental risk factors unique to a high-risk (obese and inactive) population have not been thoroughly explored. 20 Further investigation of obesogenic neighborhoods may inform the development of effective health-promoting environmental and policy interventions with the prospect of reducing morbidity, mortality and medical costs associated with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are different factors that can modify this indicator. It is suggested that age is a factor associated with a decrease in physical activity, and this is attenuated positively in trained individuals who participate in the habitual practice of physical exercise (20,21). An epidemiological study carried out in the 1980s by Heath, et al (22), supported this hypothesis by showing that physical aptitude estimated by the level of physical activity performed diminished by 9% per decade in sedentary subjects while in trained subjects, the reduction was only in the order of 5% per decade.…”
Section: Discussionmentioning
confidence: 99%